Sources of resistance to cowpea bacterial blight disease in Nigeria - Okechukwu, R.U.; Ekpo, E.J. (Wiley, 2004)
The development of resistant crop varieties depends on the reliability of the method of screening for resistance. One of the techniques widely used in evaluating field resistance is the field screening method. However, most cowpea varieties regarded as having field resistance are often found to be susceptible in farmers’ fields, where the inoculum density can be higher. This study rescreened 96 cowpea varieties, evaluated earlier in breeders’ fields as resistant to Xanthomonas campestris pv. vignicola, in field and greenhouse under high inoculum pressure. There were significant differences (P ≤ 0.05) in the reactions of cowpea varieties to bacterial blight in terms of disease incidence and severity. Results from the field screening showed that there were 69 susceptible, 25 moderately susceptible, and 2 resistant varieties. In artificial inoculation in the greenhouse IT81D‐1228‐14, IT82E‐16, IT93K‐2271‐2‐2, TVu 1235, and TVu 4630, which were moderately susceptible in the field showed a susceptible reaction. Tvu 12349 and Tvu 15549 gave consistent reactions in the field and in the greenhouse and are therefore good sources of stable resistance to bacterial blight pathogen. Stem canker incidence also varied significantly (P ≤ 0.05) among the cowpea varieties. Seventeen varieties did not manifest canker symptoms.